An investigation into the drivers and barriers for carbon emissions measurment and reduction: A stakeholder perspective - Jackson, Oliver John (2008)
In recent years climate change policy and carbon management has grown dramatically on the public agenda. Where in the past, emphasis has been focussed more on the science involved, and to what extent we as humans are affecting the environment, it is now widely accepted that anthropogenic actions are changing our climate. This in turn has led to a large scale response from business as a means of adjusting to the change in societal norms. Whilst in the past, response to climate change has been primarily concerned with political and non-market activity, huge market opportunity is now beginning to emerge.